Determining A Micro, Small And Medium Enterprises (MSME) Cluster Development Strategy Using Swot Analysis and The Business Model Canvas Approach - Alia Akhmad, Khabib; Suyatno, Agus; Alya Ayu Patricia, Bellinda (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
This research aims to formulate a strategy for developing the Micro, Small and Medium Enterprises (MSME) cluster using SWOT Analysis and the Business Model Canvas (BMC) approach. The aim of this research is to identify internal and external factors that influence the MSME cluster and map existing business models in order to formulate effective strategies. The methodology used is a qualitative approach with case studies, involving data collection through in-depth interviews, observations and literature studies. The SWOT analysis revealed key strengths such as adaptability and government support, but also identified weaknesses in technology access and management. Meanwhile, BMC helped map out the important elements of the MSME cluster business model, showing the need for product diversification and expansion of the distribution network. The findings of this research lead to a comprehensive development strategy, such as increasing technology access and market diversification, which is expected to increase the competitiveness and sustainability of the MSME cluster in the future.